Breaking the chain: An empirical analysis of accident causal factors by human factors analysis and classification system - Li, Wen-Chin; Harris, Don (Cranfield University, 2006)
This research analyzed 523 accidents in the R.O.C. Air Force between 1978 and 2002 using the Human Factors Analysis and Classification System (HFACS) framework described by Wiegmann & Shappell (2003). This study provides an understanding, based upon empirical evidence, of how actions and decisions at higher levels in the organization to result in operational errors and accidents. Suggestions are made about intervention strategies focusing on the categories at higher levels of HFACS. Specific targets for remedial safety actions should be aimed in the areas that share the strongest and greatest number of significant associations with ‘Organizational Influences’ (for example, ‘organizational process’, ‘inadequate supervision’ and ‘Crew Resource Management’). The greatest gains in safety benefit could be achieved by targeting these areas. Furthermore, this study also demonstrates that the HFACS framework is a useful tool for guiding accident investigations and for targeting potentially cost-effective remedial safety actions for breaking the chain of accidents.
Keywords: Accident Investigation; Human Error; Human Factors Analysis and Classification System